2000
DOI: 10.1152/ajplung.2000.278.5.l1039
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone induces apoptosis of human and rat alveolar epithelial cells in vitro

Abstract: The antiarrhythmic amiodarone (AM) and its metabolite desethylamiodarone (Des) are known to cause AM-induced pulmonary toxicity, but the mechanisms underlying this disorder remain unclear. We hypothesized that AM might cause AM-induced pulmonary toxicity in part through the induction of apoptosis or necrosis in alveolar epithelial cells (AECs). Two models of type II pneumocytes, the human AEC-derived A549 cell line and primary AECs isolated from adult Wistar rats, were incubated with AM or Des for 20 h. Apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
2
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 38 publications
(47 reference statements)
8
62
2
4
Order By: Relevance
“…Thus, DEA cytotoxicity in the presence of AMD was evaluated at 3 h to avoid AMD-induced cytotoxicity. Bargout et al reported that A549 cells do not express P450 monooxygenase, which plays a role in AMD metabolism, 27) and we also confirmed that DEA was not detected in a long-period uptake study of AMD in A549 cells (data not shown). Thus, the increase of cyototoxicity by the metabolism of AMD to DEA could be negligible in A549 cells.…”
Section: Effect Of Amd On Atp Content In A549 Cellssupporting
confidence: 87%
“…Thus, DEA cytotoxicity in the presence of AMD was evaluated at 3 h to avoid AMD-induced cytotoxicity. Bargout et al reported that A549 cells do not express P450 monooxygenase, which plays a role in AMD metabolism, 27) and we also confirmed that DEA was not detected in a long-period uptake study of AMD in A549 cells (data not shown). Thus, the increase of cyototoxicity by the metabolism of AMD to DEA could be negligible in A549 cells.…”
Section: Effect Of Amd On Atp Content In A549 Cellssupporting
confidence: 87%
“…Thus, low concentrations of AM µM) did not induce cell damage in HUVECs, while a high concentration (100 µM) of AM induced cell damage. Two reports discussed the induction of apoptosis by AM in human and rat alveolar epithelial cells in vitro 19) and in L-132 human lung epithelial cell lines. 20) In our study, treatment with AM (30 µM) for 4 hours in HUVECs did not induce any apoptotic cells.…”
Section: +mentioning
confidence: 99%
“…These findings correlated with a marked decrease in the cellular content of glutathione, as determined by 5CMF-DA fluorescence intensity. AMD-induced apoptosis has been shown in rat thymocytes [8], human monocytes [9], and also in different nonimmune cells, including cardiomyocytes [6], alveolar epithelial cells [2], thyroid cells [5], and hepatocytes [4]. Adverse effects of AMD on cell immune responses have been reported to be mediated by phospholipase inhibition or drug-induced oxidative stress and membrane destabilization [15,10].…”
Section: Discussionmentioning
confidence: 99%
“…The antiarrhythmic effect of AMD is derived from its multichannel blocking effects, including blocking of potassium and sodium channels and beta receptor blocking [1]. On the other hand, administration is often limited by its toxic side effects (pulmonary, liver, thyroid and cardiomyocytes toxicity), and drug withdrawal is often necessary [2][3][4][5][6]. When administered at higher concentrations, AMD induces mitochondrial swelling, collapse of the mitochondrial membrane potential [7], and apoptosis [5].…”
Section: Introductionmentioning
confidence: 99%